Theory-Inspired Rather than Theory-Based Criticism: Towards a Semeiocritical Method for the Interpretation of Literature - Besbes, Khaled (Studia Anglica Posnaniensia, 2019)
The present article is written almost a decade and a half after the reticent announcement of the death of literary theory by a number of scholars around the world. But during all these years, the humanities have not managed to drive Theory out of the seminar rooms of English departments, nor have the anti-theory proponents managed to remove it from the syllabi of English studies or even from the shelves of specialized libraries. After all these years, English studies academicians find themselves still doing Theory: holding conferences on how to conduct literary studies, organizing debates on how to launch new approaches that could possibly replace critical theories, and encouraging research into less-theorized methods of literary interpretation that could respond to the ineluctable need for a method in studying literature. For good or ill, whether we admit it or not, the echoes of literary theories continue to linger behind the scenes of all debates about literature and literary studies. The question is therefore not how to bring those echoes to silence, but rather how to find a way out of the post-theory deadlock by proposing what I have chosen to name the semeiocritical method as a theory-inspired, rather than theory-based approach to literature. The present article seeks to answer two questions: (1) how can we benefit from the lessons of literary theory without systematically doing theory or being methodically loyal to theories? and (2) how can we maximize the effects of literary interpretation in such a way as to cover as many aspects as possible of the signifying processes in the literary text while maintaining interpretive consistency?